THE COMPLIANCE LEVEL OF OFFICIALS FOR STAFF DEVELOPMENT IN LAW ENFORCEMENT OF STATE CIVIL APPARATUS DISCIPLINE AT THE GOVERNMENT OF BENGKULU PROVINCE - Agung Praja Putra; Iskandar Iskandar; Jonny Simamora (Universitas Bengkulu, 2020)
Government of Bengkulu Province is strongly committed to improve the quality of the bureaucratic reform of Apparatus Resourcesparticularly apparatus resources reform at the environment of Local Government of Bengkulu Province. Based on Attachment 1 of Regulation of the Head of the Civil Service Agency No. 21 of 2010 concerning the Implementing Regulations of Government Regulation No. 53 of 2010 on Discipline of Civil Servants, it is known that the employee dismissal procedures that violate discipline begins by calling the concerned continued with the establishment of inspection team. The results of the examination if proven to do violation, then the competent authorities impose disciplinary punishment. There have been many advances experienced by the government in the field of employment, which previously civil servants performance was rated based on patronage system where the presentation and work are preferred switched to merit systemin which the competence and performance of employees are preferred. However, there are still some violations occurred both violations of discipline and criminal.